Populism and Pop Cultures: Podemos, the Political Use of Music and the Party as a 'Pop Product' - Loris Caruso (Coordinamento SIBA, 2020)
The role of 'popular cultures' and symbolic aspects such as narratives, imaginaries, audio and visual products in the emergence, success, and development of populism is poorly explored in literature. This article aims at investigating the relationship between populism and popular cultures by analyzing the case of the Spanish party Podemos. From the beginning, for the founding nucleus of Podemos it was crucial to try to be hegemonic, to match common sense, popular attitudes and identities, and to go beyond the traditional boundaries inside which the alternative left was enclosed. The article focuses on the relationship between the political evolution of the party and its use of music as a political tool and a ground for cultural debate. The link emerges between these political uses of music and the trajectory of the party, where the latter influences the former. Moreover, by debating on the political role of music, Podemos leaders delved deeper into he wider issue of the relationship between political hegemony and popular cultures, and discussed it.